Parvovirus-induced encephalitis in a juvenile raccoon - Wünschmann, Arno (J Vet Diagn Invest, 2020)
A juvenile raccoon was euthanized because of severe neurologic signs. At postmortem examination, no significant gross lesions were present. Histologic evaluation demonstrated nonsuppurative encephalitis in thalamus, brainstem, and hippocampus, cerebellar Purkinje cell loss, as well as poliomyelitis and demyelination of the spinal cord. Parvovirus antigen–specific immunohistochemistry revealed immunopositive neurons in the brainstem, cerebral cortex, and hippocampus. A few Purkinje cells were also immunopositive. DNA extracted from formalin-fixed, paraffin-embedded brain tissue (thalamus, hippocampus, cerebral cortex) yielded a positive signal using PCR targeting both feline and canine parvovirus. Sequencing analyses from a fragment of the NS1 gene and a portion of the VP2 gene confirmed the presence of DNA of a recent canine parvovirus variant (CPV-2a–like virus) in the cerebellum. Our case provides evidence that a recent canine parvovirus (CPV) strain (Carnivore protoparvovirus 1) can infect cerebral and diencephalic neurons and cause encephalitis in an otherwise healthy raccoon. Parvovirus-induced encephalitis is a differential diagnosis of rabies and canine distemper in raccoons with neurologic signs.